2004
DOI: 10.1111/j.1473-6861.2004.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning from contemporary practice: an exploration of clinical supervision in physiotherapy

Abstract: The concept of clinical supervision as a means of professional learning and support is well known within some health and social care professions, but there is a dearth of literature related to clinical supervision and physiotherapy. The aim of this article was to report the findings of an exploratory study of clinical supervision in physiotherapy. A mixed methodological approach was adopted, through the use of self‐administered questionnaires supplemented by a small number of interviews. The findings suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…The second study, which commenced in 2000, was an exploration of clinical supervision within the physiotherapy profession (Sellars 2001). Data were generated by means of questionnaires and in‐depth interviews, conducted across sites within the National Health Service (NHS) in the United Kingdom.…”
Section: Theoretical and Empirical Basis Of Our Perspectivementioning
confidence: 99%
“…The second study, which commenced in 2000, was an exploration of clinical supervision within the physiotherapy profession (Sellars 2001). Data were generated by means of questionnaires and in‐depth interviews, conducted across sites within the National Health Service (NHS) in the United Kingdom.…”
Section: Theoretical and Empirical Basis Of Our Perspectivementioning
confidence: 99%
“…There is a limited amount of literature derived from qualitative research and even less on the experience of being a clinical educator. Some insights into being a clinical educator have emerged from several studies from nursing (e.g., Brammer, 1996;Ferguson, 1996;Lawler, 1985;Morgan, 1991;Titchen, 2000), medicine (Kilminster and Jolly, 2000), occupational therapy (Fisher and Savin-Baden, 2002), physiotherapy (Currens and Bithell, 2000;Scully and Shepard, 1983;Sellars, 2004), and a multidisciplinary study (Edwards, 1996). These studies identified a range of experiences, including the sense of loss and Table I.…”
Section: Introductionmentioning
confidence: 98%
“…Edwards, 1996;Scully & Shepard, 1983;Sellars, 2004). Edwards (1996) also included speech pathology, audiology and medical clinical educators in her study.…”
Section: Introductionmentioning
confidence: 94%
“…The many problems facing clinical or fieldwork education programs across the professions and in many countries have been widely examined in recent literature, with a call to rethink clinical education (Currens & Bithell, 2000;Fisher & Savin-Baden, 2002;Strohschein, Hagler & May, 2002). Some authors have addressed changes in the context of clinical supervision (Sellars, 2004;Spouse, 2001) but few have examined the challenges and dilemmas inherent in clinical education from the perspectives of the clinical educators themselves. Little insight has been gained from most previous (quantitative) research in clinical education into what it is like to be a clinical educator, how clinical educators conceptualise their work and interpret their roles, how *Corresponding author.…”
Section: Introductionmentioning
confidence: 97%